2020
DOI: 10.3390/polym12092071
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Polymer Damage Using Hyperspectral Imaging

Abstract: Silicone rubbers (SIRs) are common industrial materials which are often used for electrical insulation including weather sheds on non-ceramic insulators (NCIs). While SIRs are typically resilient to outside environments, aging can damage SIRs’ favorable properties such as hydrophobicity and electrical resistance. Detecting SIR aging and damage, however, can be difficult, especially in service. In this study we used hyperspectral imaging (HSI) and previously investigated aging methods as a proof of concept to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similarly, hyperspectral imaging has proven useful for the early detection of mold in food products, as shown by Farrugia et al Farrugia et al (2021) . As Bleszynski et al Bleszynski et al (2020) indicated, hyperspectral imaging can be utilized to visualize polymer damage that cannot be observed in normal color images. Medus et al Medus et al (2021) employed convolutional neural networks (CNNs) on hyperspectral images to detect contaminants and defects in food packaging.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, hyperspectral imaging has proven useful for the early detection of mold in food products, as shown by Farrugia et al Farrugia et al (2021) . As Bleszynski et al Bleszynski et al (2020) indicated, hyperspectral imaging can be utilized to visualize polymer damage that cannot be observed in normal color images. Medus et al Medus et al (2021) employed convolutional neural networks (CNNs) on hyperspectral images to detect contaminants and defects in food packaging.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperspectral imaging (HSI) can perform as an alternative method for evaluating the decomposition of polymeric materials. By combining visualization and spectroscopy techniques, HSI technology makes it possible to monitor the spectral characteristics of a sample over the entire area [11][12][13][14]. The hyperspectral image contains hundreds of different spectral responses of the same region, which provides detailed information about the spectral properties of an object and makes it possible to achieve an accurate object identification and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectrometers are also used for the characterisation of surfaces and quality control of materials 23,24 . However, hyperspectral imaging is a relatively new technology, which divides the spectrum of reflected light into multiple channels 25,26 . It has been used in various medical applications, as well as the characterisation of polymer materials, assessment of the environmental state of crops and vegetation, in dyeing recipe predictions, and even in assessments of the condition of paint in civil structures 25,27,28,29,30 …”
Section: Introductionmentioning
confidence: 99%